Pemberdayaan anggota PKK Desa Pandau Jaya dalam pembuatan pakan jamu fermentasi untuk meningkatkan kesehatan ikan budidaya - Henni Syawal; Nuraini Nuraini; Saberina Hasibuan; Syafriadiman Syafriadiman (Unri Conference Series: Community Engagement, 2019)
Pandau Jaya Village is one of the villages in Siak Hulu Subdistrict, Kampar Regency. The dedication activity was carried out in conjunction with the integrated student activities of UNRI in 2019 and in collaboration with partners (CV Bang Lele Indonesia) in the service activities. The purpose of this activity is to empower PKK members in making fermented herbal medicine, the results will be sold to CV Bang Lele Indonesia for use in feeding fish to aquaculture so as to enhance growth, health and disease resistance. The method used is, first the lecture and discussion method, namely the delivery of material related to the activities of making fermented herbs, then continued with the practice of making herbs, spreading fish seeds, and how to feed herbal medicine to fish that have been maintained by partners. The results of this community service activity, there were two participants who had succeeded in making fermented herbal medicine and immediately applied it in cultivation activities, while the other one only produced fermented herbal medicine and was sold to CV Bang Lele Indonesia. Observation of growth and survival. fish were observed for two months. The types of fish that are kept are catfish and tilapia. The results of the observations showed that the cultivated fish experienced rapid growth, that is, during the 60 days of maintenance there was an increase in the average length of 10 cm and a weight of 50 g for tilapia, whereas in catfish 12 cm and weighs 75 g.